2010
DOI: 10.3109/10428191003682734
|View full text |Cite
|
Sign up to set email alerts
|

Sequential monitoring of minimal residual disease in acute lymphoblastic leukemia: 7-year experience in a pediatric hematology/oncology unit

Abstract: We evaluated minimal residual disease (MRD) in 91 children with acute lymphoblastic leukemia (ALL) by PCR amplification of clonal rearrangements, immunoglobulin (IgH; VDJ rearrangement, CDR3 region) and T-cell receptor (TCRdelta). Sequential monitoring of MRD was performed at different time points during and after chemotherapy and was correlated to patient outcome. In total, 792 bone marrow samples were assessed for MRD at the end of induction, and during and after treatment completion. MRD positivity at the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Such studies have focused on newly diagnosed patients (5)(6)(7)(8)(82)(83)(84)(85)(86)(87)(88)(89), patients with first relapse leukemia (9,(90)(91)(92), and patients undergoing allogeneic hematopoietic stem cell transplant (HSCT) (93-96). They unanimously showed that MRD is a powerful predictor of outcome, leading to the adoption of MRD as a critical risk-assignment criteria (12,52).…”
Section: Clinical Significance Of Mrd In Pediatric Allmentioning
confidence: 99%
“…Such studies have focused on newly diagnosed patients (5)(6)(7)(8)(82)(83)(84)(85)(86)(87)(88)(89), patients with first relapse leukemia (9,(90)(91)(92), and patients undergoing allogeneic hematopoietic stem cell transplant (HSCT) (93-96). They unanimously showed that MRD is a powerful predictor of outcome, leading to the adoption of MRD as a critical risk-assignment criteria (12,52).…”
Section: Clinical Significance Of Mrd In Pediatric Allmentioning
confidence: 99%
“…The rate of clearance of leukemic cells from the bone marrow during the early phases of therapy is an independent prognostic factor in ALL. Patients who respond slowly have high risk of relapse, and patients who fail to achieve complete remission within 4-6 weeks of the induction treatment have a particularly dismal prognosis [1,5]. The poor prognosis of patients with Philadelphia positive ALL is partly due to relatively slow rate of reduction of the leukemic clone by chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations lead to the formation of a sequence that represents the hypervariable region, known as the third complementary determining region (CDR3) of the rearranged heavy chain gene. The coding sequence of CDR3 is a fingerprint-like sequence and is used as a molecular marker for the estimation of the level of MRD [1]. The rate of clearance of leukemic cells from the bone marrow during the early phases of therapy is an independent prognostic factor in ALL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and Campana, 2000). Recent studies indicated that monitoring of MRD constituted an essential prognostic marker, and that detection of MRD, particularly at the end of induction and after treatment www.intechopen.com completion, was significantly predictive for patient outcome (Katsibardi et al, 2010;Stow et al, 2010).…”
Section: Minimal Residual Diseasementioning
confidence: 99%